The Influence of Fair Value Measurement on Radical Financing of Irrational Managers Based on Fixed Effects Model and Fisher Permutation Test. (22nd February 2021) - Wang, Wei; Qu, Xiao-hui; Du, Jian-Ju; Zhu, Jia-Ming
Abstract : Adopting fair value measurement may bring more earnings fluctuations and induce irrational psychology and radical financing behavior of managers. Based on behavioral corporate governance theory, using the sample of Chinese A-share nonfinancial listed companies during 2007–2017, this paper empirically examines the regulatory effect of fair value measurement, that is, whether fair value measurement affects the company's financing decisions when managers have irrational psychological characteristics, i.e., overconfidence. The study found that overconfident managers of the company that have fair value measurement assets will be more aggressive for debt decisions, indicating that fair value measurement has a positively regulatory effect on overconfident managers.